PARTISIPASI SEKTOR SWASTA DALAM RANGKA PELAKSANAAN INVESTASI DI PELABUHAN TANJUNG PRIOK : ANALISA TERHADAP HASIL IMPI,EMENTASI LINDANGT]NDANG NOMOR 17 TAHLIN 2008 - , Adhi Kresna Novianto, SH, Prof. Dr. Nindyo Pramono, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In terms of improving the management of the flow of goods caused by inadequate port broad government costs always hit a problem and is unable to bear the entire burden of the cost of infrastructure needs in Indonesia. Therefore, other financing mechanisms available for the development and construction of infrastructure is the mechanism of Public Private Partnership (Public Private Partnership). In order to attract private investment in the Tanjung Priok port development project, the Government through Act No. 17 of 2008 on Shipping is expected to provide a boost for the private sector to increase its participation in the development of port facilities or infrastructure. This empirically explain the increase in interest and participation of the private sector of port, using Indonesia's main port, Tanjung Priok. This type of research is a kind of mixture of research (both normative legal research and empirical legal studies) with normative juridical approach is done through the selection of library materials or secondary data. The results of this study demonstrate the development of port infrastructure in Indonesia to rely on private sector confidence in the government, through Act No. 17 of 2008 which are guaranteeing and encouraging investment in port infrastructure . However, in reality evidence of success of Act No. 17 o f 2008 to increase the interest and participation of the private sector can not be proven harbor concrete . It is necessary for a survey of firms , Indonesian Chamber of Commerce ( Kadin) and the Chamber of Commerce - International Chamber of Commerce in Indonesia to find out how much investor interest in the country and abroad to invest as well as interviews with all agencies to determine barriers - barriers that governments face in a government regulation governing the related technical implementation of private participation in the construction and / or operation of infrastructure in the port of Tanjung Priok .